y/3+y/6=5/3

Simple and best practice solution for y/3+y/6=5/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y/3+y/6=5/3 equation:



y/3+y/6=5/3
We move all terms to the left:
y/3+y/6-(5/3)=0
We add all the numbers together, and all the variables
y/3+y/6-(+5/3)=0
We get rid of parentheses
y/3+y/6-5/3=0
We calculate fractions
There is no solution for this equation

See similar equations:

| 180=6x+4 | | 28+102+7x+16=180 | | 18=-2(x-2)+4x | | 28+x=2 | | 18x-3.8x=7.36x-1.9x | | 7x=24+3x= | | 9x-25+6x=6x+3x+10+7 | | 6(x-4)+3=-21 | | 3/8x=2=14 | | -4w+3{2w-1}=17 | | 8m+20=400 | | 9a-11=28 | | X-92=7(2x+3)-9 | | 3(4q+1)=-21 | | 71-y=284 | | 3x+22+5x-13+4x+24=180 | | 8m+20=440 | | 3(2m-4)/6+5=8 | | -2(4x-4)-3x+5=-90 | | 2x+25=3x-21 | | 241=72-x | | -3(x+2)+15=14-4x | | (-x)+(-3)=-13 | | -10x+(-15)x+16=17+15 | | 11-n=-20 | | 2(3x-2)+5=-6(4-x)+25 | | 4x=-84x=−8 | | -4b+6=9b-7 | | 6(p-2)=56 | | -3x+11=9 | | 27=9−3x | | 137=-y+200 |

Equations solver categories